Effect of blended method on learning achievement and development online material in curriculum information document online system (CIDOS) for computer application course. - Ismail, Norhafizah; Wan Ali, Wan Zah; Md Yunus, Aida Suraya; Mohd Ayub, Ahmad Fauzi (Universiti Sains Malaysia, 2014)
The effect on learning achievement is a vital part of the tertiary education. It can be measured by summative evaluation whether using conventional, virtual or hybrid teaching and learning method. As the learning technology transforms to a new era and so do the alternatives come to generate the smoothness and effectiveness of learning outcome.